Peningkatan pemahaman konsep membandingkan pecahan sederhana melalui model pembelajaran pair checks pada peserta didik kelas III sekolah dasar - Dewi, Rosyida; Suharno, Suharno; Adi, Fadhil Purnama (Universitas Sebelas Maret, 2019)
The purpose of the research is to improve the understanding of the concept about comparing simple fractions with the application of model pair checks. This type of research is a classroom action research conducted for two cycles. Each cycle includes the stages of planning, acting, observing, and reflecting. Data collection techniques are using tests, observations, interviews, and documentation. Data validity test techniques are using content validity, source and technical triangulation. Data analysis technique used is an interactive model. The results showed the average value of the pre-action class score of 55,55 (14,28%), in the first cycle the average value increased to 73,55 (61,90%), and second cycle the average value increased to 80,93 (90,48%). Based on the result of the research, it can be concluded that through the application of model pair checks can improve the understanding of the concept about comparing simple fractions for third grade of SDN Asinan 2, Bawen, Semarang in the academic year 2018/2019.Keywords : concept understanding, comparing simple fractions, and model pair checks